2023
DOI: 10.3390/pharmaceutics15030983
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Dissolution and Permeability Testing of Inhalation Products: Challenges and Advances

Abstract: In vitro dissolution and permeability testing aid the simulation of the in vivo behavior of inhalation drug products. Although the regulatory bodies have specific guidelines for the dissolution of orally administered dosage forms (e.g., tablets and capsules), this is not the case for orally inhaled formulations, as there is no commonly accepted test for assessing their dissolution pattern. Up until a few years ago, there was no consensus that assessing the dissolution of orally inhaled drugs is a key factor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…As mentioned previously, KETO is a poorly water-soluble drug, and its release profile is shown in Figure 6 . It is known in pulmonary delivery that the delivered medication dose must be quickly dissolved and released upon lung deposition to reduce the risk of a clearance mechanism (i.e., macrophage uptake) [ 38 , 58 ]. It is demonstrated that ~80% of the drug released from our formulations within the first 5 min, while only 11% released from the raw KETO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, KETO is a poorly water-soluble drug, and its release profile is shown in Figure 6 . It is known in pulmonary delivery that the delivered medication dose must be quickly dissolved and released upon lung deposition to reduce the risk of a clearance mechanism (i.e., macrophage uptake) [ 38 , 58 ]. It is demonstrated that ~80% of the drug released from our formulations within the first 5 min, while only 11% released from the raw KETO.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, a fast dissolution rate was achieved, in which 80% of the drug was released in 10 min due to the nanosize of the ketoprofen. In order to lower the chance of clearance mechanisms, it is well established in pulmonary administration that the administered drug needs to be rapidly dissolved and released upon lung deposition [ 38 , 58 ]. Moreover, all samples showed a significant anti-inflammatory effect and decreased IL-6 on the LPS-treated U937 cell line, with low toxicity indicating their safety.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the dissolution of orally inhaled drug formulations in DPIs was highlighted by Nokhodchi et al [ 43 ]. Pulmonary drug absorption and, consequently, clinical performance, might be limited by the dissolution or release processes.…”
Section: Resultsmentioning
confidence: 99%
“…The solubility and poor solubility of the molecules determine the variation in classification. In particular, in vitro dissolution studies or in vivo permeations studies have been carried out [ 101 ]. Specifically, using these drugs that are produced using safe methods is always of great environmental interest.…”
Section: Pharmacological Speciesmentioning
confidence: 99%